1992
DOI: 10.1021/bi00142a005
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of a cDNA clone encoding the zinc metalloproteinase hemorrhagic toxin e from Crotalus atrox: evidence for signal, zymogen and disintegrin-like structures

Abstract: The sequence of two overlapping cDNA clones for the zinc metalloproteinase hemorrhagic toxin e (also known as atrolysin e, EC 3.4.24.44) from the venom gland of Crotalus atrox, the Western diamondback rattlesnake, is presented. The assembled cDNA sequence is 1975 nucleotides in length and encodes an open reading frame of 478 amino acids. The mature hemorrhagic toxin e protein as isolated from the crude venom has a molecular weight of approximately 24,000 and thus represents the processed product of this open r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 48 publications
1
74
0
3
Order By: Relevance
“…Similarly, as in the matrix metalloproteinases, a cysteine-switch mechanism has been proposed for these enzymes (Hite et al, 1992;Grams et al, 1994).…”
Section: Proenzyme Activationmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, as in the matrix metalloproteinases, a cysteine-switch mechanism has been proposed for these enzymes (Hite et al, 1992;Grams et al, 1994).…”
Section: Proenzyme Activationmentioning
confidence: 94%
“…In their venom glands, snakes of the family Crotalidae (adders) produce extremely aggressive proteolytic enzymes, which can cause hemorrhage and tissue necrosis (see reviews by Bjarnason Takeya et al, 1990;Hite et al, 1992Hite et al, , 1994Kini & Evans, 1992). These toxins have been named adamalysins after adamalysin 11, an enzyme from the rattlesnake Crotalus adamanteus (Gomis-Ruth et al, 1993a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, an analysis of the depth or the distance between the S' 1 -pocket and the catalytic site cavity revealed no significant differences or correlation to hemorrhagic activities for the C. s. scutulatus metalloproteinase models. While the atrolysins have been characterized as hemorrhagic toxins that cleave similar substrates in vitro [55,56], the fact that their catalytic clefts superimpose well with each other but poorly to weakly hemorrhagic C. s. scutulatus metalloproteinases is consistent with this observation.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, there are metalloproteinases in snake venoms which are devoid of hemorrhagic activity (Willis & Tu 1988, Markland 1998. The structural basis of this observation is not clear, although some comparative studies have identified residues which may be required to exert this activity (Takeya et al 1990, Hite et al 1992, Ramos & Selistre-de-Araújo 2004.…”
mentioning
confidence: 99%